Making Meaning: Indigenous Legal Education and Student Action - Borrows, John (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2022)
Law students help universities and societies make meaning and purpose, particularly as it relates to Indigenous and Canadian law. They do this through their questions, research, committee work, service, career paths, and past experiences. Some of their insights are found in the unfolding of Indigenous legal education initiatives at the University of British Columbia, Osgoode Hall Law School at York University, the University of Toronto, and the University of Victoria. These initiatives illustrate that law students are a significant force in persuading law schools to add Indigenous courses, moot courts, clinical experiences, internships, landbased events, scholarly journals, and teaching Indigenous legal traditions. In the process, these developments have implications for questions like why we are here and where we are going in our broader legal and political circles. As student action is changing how we teach and practice law in Canada, this essay examines ways in which meaning is more generally made in contextual terms, even as we struggle with the idea that law (and life) has broader, universal purposes.